BIRDS OF POZO LIZAS BEACH, PROVINCE OF ILO, SOUTH PERU - Pizarro-Neyra, José (2015)
The avifauna of Pozo Lizas beach, in southern Peru, has been little studied. This zone reaches importance for the conservation of migratory birds and is located in the surroundings of the marine protected area of Punta Coles. Part of Pozo Lizas is a sandy beach more than 5 km long and of variable width. At the north end, there are some rocky shore patches. The author made observations of birds in this zone during 2009-2015 accumulating 40 h of observations in twelve field trips. The results show that 24 aquatic birds and 4 terrestrial birds were observed. The species sighted most frequently were Larus modestus, Phalacrocorax bouganvillii and Pelecanus thagus. The present work is the first report on birds of Pozo Lizas beach in the last ten years.